Pengaruh Gerakan Literasi Sekolah Terhadap Minat Membaca Dalam Bentuk Pojok Baca Siswa di Sekolah Dasar Kelas IV UPT SDN 12 Arungkeke Kabupaten Jeneponto - Nanda Putri Sagita; H. Yuddin Passiri; Akbar Avicenna (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
The formulation of the problem in this research is what is the influence of the school literacy movement in the form of a reading corner on students’ reading interest in grade IV elemetary school UPT SDN 12 Arungkeke Kabupaten Jeneponto? The aim of this research is to identify the influence of the school literacy movement in the form of a reading corner on students’ interest in reading in grade Ivelementary schools at UPT SDN 12 Arungekeke Jeneponto. Regency the type of research method used is quantitative research. The data collection process uses questionnaires,interview and documentation. The results of this research illustrate that the reading corner value data and reading interest show a positive influence from the reading corner variable. So that there is an increase in the value of reading corners which ha a positive effect on increasing students’ interest in reading. With the existence of the school literacy moment programs, efforts to improve the service and quality of reading corners in classes organized by schools will certainly influence students’ interest in reading.